2015
DOI: 10.1371/journal.pone.0141244
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Diagnosis of Testicular Cancer; A Need for Awareness Programs

Abstract: Background AimTo gain insight into patient and doctor delay in testicular cancer (TC) and factors associated with delay.Materials and MethodsSixty of the 66 eligible men; median age 26 (range 17–45) years, diagnosed with TC at the University Medical Center Groningen completed a questionnaire on patients’ delay: interval from symptom onset to first consultation with a general practitioner (GP) and doctors’ delay: interval between GP and specialist visit.ResultsMedian patient reported delay was 30 (range 1–365) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
4
37
0
1
Order By: Relevance
“…A patient interval of 3 months or longer was associated with a late diagnosis of NPC, which agreed with the findings of similar studies in which physical examination and knowledge about early symptoms played important roles in reducing the patient interval and promoting diagnosis at an early stage [ 36 , 37 ]. In the present study, physical examination was also associated with early NPC diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…A patient interval of 3 months or longer was associated with a late diagnosis of NPC, which agreed with the findings of similar studies in which physical examination and knowledge about early symptoms played important roles in reducing the patient interval and promoting diagnosis at an early stage [ 36 , 37 ]. In the present study, physical examination was also associated with early NPC diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…The study by Öztürk confirmed that the relationship between one's education and tumor detection is more significant than in case of age or financial status. The second important reason is the embarrassment which restrains patients from consulting the doctor [16]. In the current study the ambivalent approach of the respondents was revealed.…”
Section: Discussionmentioning
confidence: 60%
“…Potwierdza to analiza Öztürka, która wykazała, że niski poziom edukacji ma większy wpływ na opóźnienie diagnozy w porównaniu z czynnikami takimi jak wiek czy status materialny. Drugi istotny powód wskazany przez Öztürka to onieśmielenie przyczyniające się do odwlekania konsultacji potencjalnych zmian chorobowych z lekarzem [16]. W badaniu na grupie populacji lubelskiej wykazano mieszany stosunek respondentów do tej tematyki.…”
Section: Pielęgniarstwo XXI Wiekuunclassified
“…The USPSTF (2011) states that males typically detect TCa unintentionally or through self/partner examination. Other research suggests that the best outcomes for TCa treatment stem from cases treated in earlier stages of the disease (see Saab et al, 2014 , Gilligan, 2015 , Öztürk et al, 2015 ). It would therefore be logical to assume that TSE or clinician examination promotes optimal wellness within this population.…”
Section: Inconsistencies In Logic Language and Methodologymentioning
confidence: 99%